KARAKTERISTIK ‘TEH SUSU’ KOMBINASI SEDUHAN DAUN TORBANGUN DAN BIJI FENUGREEK SERTA SUSU ALMOND YANG BERPOTENSI SEBAGAI MINUMAN KESEHATAN IBU MENYUSUI [CHARACTERISTICS OF 'MILK TEA' A COMBINATION OF TORBANGUN LEAVES AND FENUGREEK SEEDS STEEP ALONG WITH ALMOND MILK WHICH HAS THE POTENTIAL AS A HEALTH DRINK FOR BREASTFEEDING MOTHERS] - Mastuti, Titri Siratantri; Djuarsa, Veronica Angelia; Matita, Intan C. (Universitas Pelita Harapan, 2024)
Torbangun leaves (Plectranthus amboinicus L.), fenugreek seeds (Trigonella foenum-graecum L.), and almond milk are widely used in the form of functional food or beverages to increase breastmilk production and serve as sources of antioxidants. The utilization of torbangun leaves as a functional beverage product is still limited compared to fenugreek seeds and almond milk. This study aimed to create ’milk tea’ as a health drink consisting of torbangun leaves, fenugreek seeds, and almond milk, and to analyze the physicochemical characteristics and sensory evaluation results of each mixture. The factors investigated were three types of steeping water, namely torbangun leaf steep, fenugreek seed steep, combination steep. In addition, there were four ratios of almond milk to steeping water (0:1, 1:1, 2:1, 1:2). The analysis parameters were antioxidant activity, total phenolic content, and total flavonoid content. The selected product was a drink with almond milk and a combination of steeping water (torbangun leaves and fenugreek seeds) with a ratio of 1:2. This product was chosen considering the antioxidant activity results with an IC50 value of 793.99 mg/L; total phenolic content of 1441.56 mg/L; and total flavonoid content of 950 mg/L, which were higher compared to functional beverages with different ratios in combined steeping water or torbangun leaf steep, supported by sensory evaluation results. The selected treatment drink had a relatively high mineral content, namely calcium 7.38 mg/100 mL, magnesium 7.28 mg/100 mL, potassium 36.02 mg/100 mL, and iron 0.72 mg/100 mL.Bahasa Indonesia Abstract:Daun torbangun (Plectranthus amboinicus L.), biji fenugreek (Trigonella foenum-graecum L.), dan susu almond banyak digunakan dalam bentuk minuman fungsional untuk meningkatkan produksi ASI dan sebagai sumber antioksidan. Pemanfaatan daun torbangun sebagai produk minuman fungsional masih terbatas dibandingkan dengan biji fenugreek dan susu almond. Penelitian ini bertujuan untuk membuat ’teh susu’ sebagai minuman kesehatan yang terdiri dari daun torbangun, biji fenugreek, dan susu almond serta menganalisis karakteristik fisikokimia dan hasil uji sensori dari setiap campuran. Faktor yang diteliti adalah tiga jenis air seduhan, yaitu seduhan daun torbangun, seduhan biji fenugreek, dan seduhan kombinasi. Selain itu, terdapat empat rasio susu almond terhadap air seduhan (0:1, 1:1, 2:1, 1:2). Parameter analisis berupa aktivitas antioksidan, total kandungan fenolik, dan total kandungan flavonoid. Produk yang terpilih adalah minuman dengan susu almond dan kombinasi air seduhan dengan rasio 1:2. Produk ini terpilih dengan mempertimbangkan hasil aktivitas antioksidan dengan nilai IC50 793,99 mg/L; total kandungan fenolik 1441,56 mg/L; dan total kandungan flavonoid 950 mg/L yang lebih tinggi dibandingkan dengan minuman fungsional dengan rasio lain pada seduhan air kombinasi atau seduhan daun Torbangun, serta didukung oleh hasil uji sensori. Minuman dengan perlakuan terpilih memiliki kandungan mineral cukup tinggi yaitu kalsium 7,38 mg/100 mL, magnesium 7,28 mg/100 mL, kalium 36,02 mg/100 mL dan zat besi 0,72 mg/100 mL.